Administrative Delicts and Administrative Delict Law - P. E. Spiridonov (Сибирское юридическое обозрение, 2020)
The subject of study in this paper are administrative-delict legal relations and the terms associated with this kind of relations. The purpose of the study is to analyze the nature of offences and administrative delicts. It is stated that the use of the term “delictum” it's been a certain evolution from private legal term in the sense of “delicta private” to the term, which can be used both in the sense of “delicta private” and value of “delicta publica”. The conclusion is that the term “delict” may be used in public relations and administrative legal use of the term “administrative delict”. Expanding the range of investigated administrative and delict relations, entails a change and the essential characteristics of administrative offenses, and also creates preconditions for formation of administrative-tort system of prevention of offenses, including not only administrative offences but also other offences that are not related to crimes and civil offenses. In this case, the responsibility should be named administrative and delict, which, in essence, will include a modern administrative and administrative-disciplinary liability. Depending on the nature of the administrative delict may be subdivided into administrative offense and administrative misdemeanor. The essential characteristics of an administrative offense should be upheld, and administrative misdemeanor must be attributed those acts which are now administrative and disciplinary misconduct. With this division of administrative delicts it is possible to realize a codification of administrative and delict legislation, i.e. the creation of Administrative-delict code of the Russian Federation. The work also made the assumption that procedural violations are treated as administrative delict. An attempt is made to distinguish between material legal relations in administrative law and administrative procedural legal relations. Concluded that you cannot mix administrative-tort legal relations, as a kind of material with tort and procedural legal relations. In turn, tort and procedural legal relations are an integral part of administrative and legal proceedings, and administrative delict production is an integral part of the administrative process. The methodological basis of the article is dialectical, formal logical methods, formal-legal method and method of interpretation of law.